A influência da perícia judicial contábil conclusiva para o embasamento da decisão judicial - Silva, Marcelo Borghi Moreira da (2021)
With the uninterrupted development of the forensic practices, seeking through those the improvement of the methods for its verification, accounting expertise as an element of judicial evidence, is a necessary instrument for the delineation of the issue raised in court and for the outcome of the judicial process. This work is based on the analysis, verification and ascertainment of the influence of the technical report, developed by a registered judicial expert before the National Register of Accounting Experts (CNPC), on the judicial decision, thus taking into consideration the approach and the conclusion of the technical work since the accounting expert must necessarily be a legally, culturally and intellectually skilled as well as committed to the truth professional. Therefore, it is from the essence of the report that it contains conclusive answer as well as it is expressly established that the judge when considering the expert evidence must indicate in the sentence the reasons that led him to consider or not to consider the conclusions of the report. In order to analyze the data were consulted the lawsuits processed under the digital form before the 18 Courts of the Public Treasury of the Capital of the State of São Paulo and that contained expert accounting reports, thus excluding the lawsuits that presented other types of reports, such as medical, criminal, engineering, graphotechnical, computer, psychology or environment reports. From the total of 206 lawsuits with accounting expertise, 81 of them were identified as containing delivered sentences. Among these lawsuits with pronounced decisions and accounting expert reports, all of them were analyzed in order to verify the existence or the absence of conclusion in the referred expert reports and whether they were prepared by accounting experts registered on the Regional Accounting Council (CRC) and the National Register of Accounting Experts (CNPC), as well as whether the issued sentences were reasoned on the expert reports and the rectified indexes of the rulings due to the filing of an appeal before the Court of Justice of the State of São Paulo (TJSP). From the verification of the referred accounting expert reports and the issued sentences that considered or not the expert conclusions, in a motivated or not motivated way, it was verified that 75% of the pronounced sentences were based on the developed expert reports, as well as that 14% of the issued decisions reasoned on the referred reports were modified by the Court of Justice on appeal. It was also observed that 10% of the expert accounting reports were elaborated by professionals not registered on the CNPC. As a recommendation, the present work may be used as an instrument of reflection on the current mechanism of accounting expertise and its confrontation in a conclusive manner by both judicial experts and magistrates, as well as a reflection on accountability and ethical conduct in the performance of the taking the evidence by unauthorized professionals